An Overview on COVID-19 Pandemic: from Discovery to Treatment - Panati, Kalpana; Tatireddygari, Venkatramana R. A.; Narala, Venkata R. (Infectious Disorders - Drug Targets, 2021)
Recently, novel coronavirus infection (COVID-19) emerged in Wuhan, China has been declared as pandemic by WHO. Until now, no evidence is documented regarding its wild animal reservoir or intermediary host, but, human-to-human transmission, asymptomatic carriers were very much observed. The number of confirmed cases and death toll have been increased almost all over the world indicating its potential threat to public health. Though the phylogenetic analysis shows some similarity of SARS-CoV2 to bat betacoronaviruses, it exhibited significant variation in S1 domain of spike protein from bat-derived viruses. S1 domain plays an important role in receptor binding and it can be a target for the development of therapeutics and vaccines. In this review, we have discussed the updates on transmission, diagnosis, genome analysis and comparison, treatment options and clinical trials of COVID-19.
Keywords: coronavirus pandemic